Sales tax competition and a multinational with a decreasing marginal cost - Alexei Alexandrov; Özlem Bedre-Defolie (European School of Management and Technology (ESMT), 2011)
We examine a multinational firm which has a decreasing marginal cost, and the optimal sales tax policies of the regions where that firm operates. We show that the regions set higher sales taxes than those given by a cooperative equilibrium. Each region fails to fully internalize the effects of its tax level on another region's welfare and the incentives for that region's authority. Exponential cost functions which exhibit economies of scale (for example Cobb-Douglas) and linear demand functions satisfy our assumptions. Our results suggest the need to coordinate sales tax levels between countries and between smaller entities, like states in the United States. Smaller regions benefit more from such coordination. Lowering sales taxes in each region increases welfare for all regions, profits for firms, and consumer welfare.
urn:nbn:de:101:1-201106143739
Keywords: F12; F23; H25; H71; 650; tax competition; sales taxes; multinationals; decreasing marginal cost; economies of scale; Multinationales Unternehmen; Grenzkosten; Steuerwettbewerb; Umsatzsteuer; Skalenertrag; Theorie